The Influence of Policies and Regulations on Food Security and Agribusiness through Human Resource Management Using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) Approach - Dr. Abdul Wahab Samad (PT. Mega Mas Abadi Konsultan, 2025)
The aim of this study is to analyze the influence of policies and regulations on food security and agribusiness, while exploring the impact of other factors such as education and training, investment and resources, and technology and innovation, all within the context of Human Resource Management (HRM) using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The analysis results show that Policies and Regulations (X1) have a significant effect on Food Security and Agribusiness (Y1) with a path coefficient of 0.498, while Investment and Resources (X3) show a small negative influence (-0.042). This model explains 76% of the variability in Y1 (food security). Reliability and validity testing shows that most constructs have Cronbach’s Alpha, RhoA, and RhoC values greater than 0.7, indicating good reliability. This research emphasizes the importance of effective HR policies in supporting food security, although the impact of several variables such as investment and technology still needs to be further explored